The myotubularin related proteins and the untapped interaction potential of their disordered C-terminal regions - Saar, Daniel; Lennartsson, Caroline L. E.; Weidner, Philip; Burgermeister, Elke; Kragelund, Birthe B. (Proteins, 2025)
Intrinsically disordered regions (IDRs) of proteins remain understudied with enigmatic sequence features relevant to their functions. Members of the myotubularin-related protein (MTMR) family contain uncharacterized IDRs. After decades of research on their phosphatase activity, recent work on the C-terminal IDRs of MTMR7 revealed new interactions and important new functions beyond the phosphatase function. Here we take a broader look at the C-terminal domains (CTDs) of 14 human MTMRs and use bioinformatic tools and biophysical methods to ask which other functions may be probable in this protein family. The predictions show that the CTDs are disordered and carry short linear motifs (SLiMs) important for targeting of MTMRs to defined subcellular compartments and implicating them in signaling, phase separation, interaction with diverse proteins, including transcription factors and are of relevance for cancer research and neuroscience. We also present experimental methods to study the CTDs and use them to characterize the coiled coil (CC) domains of MTMR7 and MTMR9. We show homo- and hetero-oligomerization with preference for MTMR7-CC to form dimers, while MTMR9-CC forms trimers. We relate the results to sequence features and make predictions for the structural landscape of other MTMRs. Our work gives a broad insight into the so far unrecognized features and SLiMs in MTMR-CTDs, and provides the basis for more in-depth experimental research on this diverse protein family and understudied IDRs in proteins in general.
Erstmals veröffentlicht: 30. November 2024
Gesehen am 03.04.2025